Augmented Reality-Assisted IPAS Teaching Materials Oriented to Satua Bali to Improve Critical Thinking Skills of Fifth Grade Elementary School Students - Putu Astrita Dewi Putu Astrita Dewi; I Gede Margunayasa; I Wayan Widiana (Universitas Pendidikan Ganesha, 2026)
Science education in elementary schools requires students to think critically in order to understand natural and social phenomena. However, abstract material is often difficult to understand without the support of concrete learning media. This study aims to develop Augmented Reality-assisted science teaching materials oriented towards Satua Bali to improve the critical thinking skills of fifth-grade elementary school students. This study used the Research and Development method with the ADDIE model. Data were collected through interviews, questionnaires, and critical thinking ability tests using instruments that met the criteria. Data analysis techniques included quantitative descriptive analysis, qualitative descriptive analysis, and inferential statistics. The validation results showed a material expert score of 3.8 and a media expert score of 3.87, which is categorized as very good. Teacher response reached 95%, individual testing reached 94%, and small group testing reached 91.7%, which is categorized as very practical. The effectiveness test showed a significance value of 0.000 (<0.05), indicating a significant increase in students' critical thinking skills. Thus, the teaching materials developed are feasible, practical, and effective for use in IPAS learning in elementary schools.